An investigation of fraction sense among Form One students : a qualitative study - Tee, Sean Sean; Bakar, Md. Nor (2005)

(untitled)
Fraction is an important concept and considered to be a prerequisite to other topics in Mathematics. The goal of this study is to gain a better understanding of the sense of fraction, in particular, to understand the sense of orderliness of fractions that students possessed. Six selected Form One students were interviewed individually. Most of the students showed the sense of fraction towards denominator, where they were able to state the inverse relationship between denominator and fraction size. However, some of these students could not associate the information that they gained from denominator with nominator, which caused them to have the difficulty to determine the exact fraction size. Similar problem occurred when students were to compare the size between two fractions. The findings found in this study may have some direct implications for the teaching of fraction and also other mathematical concepts. More specifically, it suggests that teaching should focus on understanding and not rote memorization of facts and procedures.